Japanese encephalitis vaccine-facilitated dengue virus infection-enhancement antibody in adults. Issue 1 (December 2016) - Saito, Yuka; Moi, Meng; Takeshita, Nozomi; Lim, Chang-Kweng; Shiba, Hajime; Hosono, Kuniaki; Saijo, Masayuki; Kurane, Ichiro; Takasaki, Tomohiko
Abstract Background Dengue virus (DENV) and Japanese encephalitis virus (JEV) belong to the genusFlavivirus, and infection with a virus within this genus induces antibodies that are cross-reactive to other flaviviruses. Particularly in DENV infection, antibodies to DENV possess two competing activities: neutralizing activity and infection-enhancing activity. These antibody activities are considered central in modulating clinical outcomes of DENV infection. Here, we determined the neutralizing and infection-enhancing activity of DENV cross-reactive antibodies in adults before and after JE vaccination. Methods Participants were 77 Japanese adults who had received a single dose of inactivated Vero cell-derived JE vaccine. A total of 154 serum samples were obtained either before or approximately a month after a single dose of JE vaccination. The antibody-dependent enhancement (ADE) activity to each of four DENV serotypes and the neutralizing activities to DENV and to JEV were determined in each of the serum samples by using baby hamster kidney (BHK) cells and FcγR-expressing BHK cells. Results A total of 18 post-JE immunization samples demonstrated cross-reactivity to DENV in an anti-DENV IgG ELISA. DENV neutralizing antibodies were not detected after JE vaccination in this study. However, undiluted post-JE vaccination serum samples from 26 participants demonstrated monotypic and heterotypic ADE activity to DENV. ADE activity was also observed in 1:10-diluted samples from 35 of the JE vaccine recipients (35/77, 45 %). Conclusion In summary, JE vaccination induced DENV cross-reactive antibodies, and at sub-neutralizing levels, these DENV cross-reactive antibodies possess DENV infection-enhancement activity. The results also indicate that cross-reactivity to DENV is associated with high levels of JEV neutralizing antibodies and, the DENV cross-reactivity is further facilitated by JE vaccination.